Nanomaterial for the control of rheological properties of hydrolyzed polyacrylamide based polymeric solutions (2020)
Enhanced oil recovery (EOR) processes were developed as a strategy to extend the productivity of mature reservoirs. Polymer flooding-based HPAM is the EOR process more implemented due to its relatively low cost and operational flexibility; however, the degradation and retention in the reservoir are the main challenges. Several copolymers of polyacrylamide have been proposed to mitigate polymer deficiencies in “hard” conditions; however, these technologies are limited to favorable pricing scenarios. Nanotechnology has attracted widespread interest for use in recovery processes. Nanoparticles (NPs) incorporate new properties into traditional technologies applied in EOR. Polymer-based nanofluids or polymeric nanofluids consist of a combination of nanoparticles with polymeric solutions. Polymeric nanofluids are of great interest because they combine the advantages of inorganic NPs and organic polymers, generating synergy between the best of each of the two materials. Although numerous studies have shown a high potential of polymeric nanofluids, little evidence is available about the stability of polymeric microstructure exposed at thermal degradation, adsorption, and deformations caused by converging-diverging flow in pores. Hence, the main objective of this study is to characterize the rheological behavior of polymeric nanofluids formed by solutions of HPAM and SiO2 nanoparticles under the instability of the microstructure due to thermal degradation and concentration losses. This study provides crucial evidence about the stability of polymeric nanofluids and offers an understanding of its performance in the porous medium. Finally, it opens the landscape about the use of nanofluids in IOR/EOR processes. (Tomado de la fuente)